Entrepreneurial Litigation and Venture Capital Finance. (31st October 2017) - Cumming, Douglas; Haslem, Bruce; Knill, April
Abstract : This article empirically examines the interaction between entrepreneurial plaintiff firm litigation and venture capital (VC). The data indicate that, relative to nonplaintiffs, firms that litigate prior to (after) obtaining VC i) receive financing from less (more) reputable venture capitalists (VCs), ii) are subject to greater (similar) oversight by VCs, iii) receive less (more) VC funding, iv) are more likely to exit through an initial public offering than through an acquisition, and v) are less likely to be liquidated when litigation occurs after VC financing. The results are robust to different specifications, methodologies, and endogeneity checks.